Pathogenic diversity, ecology, epidemiology, and management practices of the potato bacterial wilt (Ralstonia solanacearum) disease - Girma Ababa (Cogent Food & Agriculture)
A bacterial wilt disease (R. solanacearum) severely damages potato crops. The pathogen infects several crops in various agroclimatic areas, and it has a broad pathogenic diversity. Six phylotypes, twenty-three sequevars, five races, and six biovars have been identified to indicate the pathogenic diversity of the pathogen. Twenty-eight isolates of Phylotype II were separated into seven classes and identified 97.06% diversity. It survives in the soil for a long time. Temperature and soil moisture, affected the infection, growth, and epidemics of the pathogen. In the last three decades, scholars have reported Mondial, CIP385312-2, Cruza 148, and CIP388285-14 resistant clones and cultivars. Five quantitative trait loci responsible for resistance were identified on different potato chromosomes. LYZ‐C resistance gene and the receptor kinase gene CLAVATA 1 were used to develop potato resistance. For potato resistance, a clustered regularly interspaced short palindromic repeat has been used since bacteria do not have Ribonucleic acid interference. Biochar, compost, and bio-organic fertilizer cultural practices are important to control the disease. It has been stated that bacteria exceed fungus as a biological control. Moreover, new or unusual biological controls such as Enterobacter sp., Pseudomonas sp., and Paenibacillus sp have been suggested. Several studies showed the effects of cultural and physical practices on other soil-borne diseases, however not on the potato bacterial wilt disease. Resistant potato clones against bacterial wilt disease are not available in developing countries. Then, the current review was proposed to assess various findings available on potato bacterial wilt pathogenic variability and management practices.